IoT-based Embedded System for Data Acquisition and Monitoring Measurement Data Methane Concentration, Humidity, and Temperature on Peatland - Iwan Sugriwan; Melania Suweni Muntini; Yono Hadi Pramono (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2027)
Abstract. In the context of the Industrial Revolution 4.0, characterized by integrating digital technologies into all aspects of our lives, developing innovative environmental devices for analyzing and monitoring methane gas concentration, air humidity, and temperature from peatland has become increasingly significant. Methane (CH4) is a major contributor to greenhouse gases, alongside carbon dioxide (CO2) and nitrous oxide (N2O), and is emitted by peatlands. The proposed IoT-based embedded system, a key component of the Industrial Revolution 4.0, plays a crucial role in data acquisition and displaying measurement data online. TGS2611 is a sensor device that detects methane concentration, and DHT22 is a device that senses humidity and temperature. Both sensor modules, TGS2611 and DHT22, are connected to the Node MCU ESP8266 as a microcontroller and a Wi-Fi module. Node MCU ESP8266 is also connected to an LCD 20x4 character to display methane concentration, humidity, and temperature. Wi-Fi signal connected to the three parameters from the Node MCU ESP8266. ESP8266 accesses the SSID address and password on the server computer. The database system built with MySQL to show methane concentration, temperature, and humidity on the server computer receives the measurement results data.; we developed a web page with HTML, CSS, JavaScript, and PHP to access the measurement data results on a database system.